KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYYAH JAMIATUL JARIYAH TEMBILAHAN HULU - Yohadi; Irjus Indrawan; Jauhari; Ahmad Juhardi; Agung Setiabudi (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
Leaders are the spearhead of madrasa progress. The lack of ability of the Madrasah principal to make decisions about the types of changes that must be made in the school as well as the lack of discipline of the Madrasah principal in participating in school activities, causes scheduled activities in the Madrasah to not run optimally. Improving the quality of education aims to maintain and improve quality in a sustainable manner which is carried out systemically to meet the needs of stakeholders, raising awareness that improving the quality of management is the responsibility of all components of society, and with a focus on continuous quality improvement at the educational institution level. The method for this service is to use qualitative methods by directly observing the conditions existing at Madrasah Ibtidaiyyah Jamiatul Jariyah. Through this observation and dedication, students can find out the performance of the Madrasah Head at the institution, so that students can help with activities that will be carried out at the Madrasah in an effort to improve the quality of the Madrasah itself. By improving the quality of Madrasahs, Madrasahs will progress and develop.